Analysis of the Millennial Generation's Interest in Reading Print Media Journalism in the 4.0 Era - Zahara J, Ayu; Saragih, M. Yoserizal (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Reading is a crucial activity that can broaden horizons and increase insight. In this digital era, reading interest faces various obstacles, ranging from minimal demand for reading to the rise of social media, and reading materials that are only skimmed because they are not interesting. This study aims to analyze the interest in reading print media journalism among the millennial generation in the 4.0 era. This study uses a qualitative approach with a phenomenological method to understand the current social phenomenon, one of which is the reading interest of the millennial generation in print media in the context of developments in the digital era. Data were collected through in-depth interviews with nine respondents including the millennial generation in Medan City which were taken using random sampling techniques. All the data that had been collected was then analyzed using the Miles & Huberman analysis technique with the stages of data collection, data reduction, data presentation, and conclusions. The themes of the findings regarding the Millennial Generation's Reading Interest in Print Media Journalism in the 4.0 Era are: i) changes in interest in reading print media, ii) characteristics of media consumption by the millennial generation, iii) factors influencing reading interest. Therefore, interest in reading print media has decreased significantly, due to the ease of access and speed of information from digital media. The millennial generation prefers digital platforms such as social media and video streaming which provide a more dynamic and relevant experience. However, print media still impresses in certain contexts, but the dominance of digital media is getting stronger in the daily lives of the millennial generation.